Soil Phosphorus Heterogeneity Improves Growth and P Nutrition of Norway Spruce Seedlings - Prietzel, Jörg (Frontiers in Forests and Global Change, 2020)
Phosphorus (P) nutrition of forest trees depends on soil P supply, which is poor on sites with sandy, quartz-rich soils and shallow calcareous soils. Soil P is distributed heterogeneously at different spatial scales. I tested the hypothesis that in P-limited forest ecosystems soil P enrichment in hotspots results in improved tree P nutrition and growth compared to soils where the same P amount is distributed evenly. In two field P fertilization experiments, Norway spruce (Picea abies) and European beech (Fagus sylvatica) seedlings were grown in soils with experimental homogeneous or heterogeneous P enrichment. The soils were amended with P to equal amounts of total P, but different patterns of P enrichment and/or as different P forms (orthophosphate [oPO4]; inositol hexaphosphate [IHP]). One experiment (Achenpass) was conducted with P-poor calcareous soil material of a Rendzic Leptosol (low-P soil), the other (Mitterfels) with Bw horizon material of a Cambisol that had formed on silicate bedrock and was characterized by moderate P concentrations (moderate-P soil). Half of the spruce seedlings additionally received experimentally elevated N deposition. At the low-P calcareous site, shoot and foliage biomass as well as foliar P, N, and S amounts of Norway spruce seedlings were considerably (+70–80%) and significantly larger on soils with spatially heterogeneous compared to homogeneous P distribution. Elevated N deposition reduced soil P heterogeneity effects on spruce by improving seedling growth on soils with homogeneous P distribution. No soil P form diversity effects were observed for spruce seedlings on calcareous soil. At the silicate site with moderate P supply, all seedlings showed excellent P nutrition. Here, only marginal, insignificant positive effects of heterogeneous soil P distribution were observed for the growth of spruce and beech seedlings without elevated N deposition, but foliar P concentrations of spruce seedlings increased significantly. Elevated N deposition resulted in a positive effect of heterogeneous vs. homogeneous soil P distribution on spruce growth (+39%; eta squared: 0.163; p=0.135) and P nutrition. Our results showed that soil P concentration heterogeneity is beneficial for spruce growth and P nutrition at sites with P-poor calcareous soils, and at silicate sites with ongoing N eutrophication.